Modeling and Simulation of Proton Beam Therapy by using Geant4/GATE (Journal of Nuclear Technology in Applied Science, 2019)
Proton Therapy is one of the most advanced cancer radiotherapy techniques. It offers more accurate dose deposition than conventional radiotherapy techniques, and therefore requires convenient procedures for quality assurance. In this technique, a Spread Out Bragg Peak (SOBP) is produced to establish a uniform dose distribution over the tumor volume. In order to produce a SOBP, several pristine Bragg peaks of different entrance energies and hence different ranges, with certain intensities (weights) should be combined together. In a passive beam scattering system, a mono-energetic pencil beam is extracted from an accelerator, and its diameter is modified by different scattering sheets. Next, a SOBP is produced by using energy modulation devices such as a Range Modulator Wheel (RMW) consisting of steps of variable thicknesses and angles, or by using a ridge filter. In this work, the Geant4/GATE application was used to simulate a typical passive scattering beamline system. To validate the developed model, the CATANA transport beamline of the INFN-LNS in Catania, Italy, was simulated in GATE. A set of pristine Bragg peaks were obtained from the MC simulations by using PMMA range shifters of different thicknesses. A mathematical algorithm was used with the simulated pristine dose profiles as its inputs, in order to calculate the weight of each pristine Bragg peak, and hence to obtain the required angular span of each RMW step. As a result, a SOBP was produced to ensure a flat dose distribution in a water phantom. Once the designed RMW was realized, the simulated dose distribution from a 62.8MeV proton beam was compared successfully with the experimental results from the CATANA facility. Other RMWs which correspond to different entrance energies (50, 60, 70, 80, 90 and 100MeV) useful for the treatment of eye and brain tumors were newly designed and tested in this study to demonstrate the valid energy range of this technique. Multiple RMWs were mathematically designed to produce plateau sizes at nearly 20%, 40% and 60% of the total depth of the original proton beam Bragg peaks.
Keywords: Proton Therapy; Range Modulator; Bragg Peak; Monte Carlo Simulation